Analisis Medan Makna Aktivitas Tangan Dan Kaki Dalam Kamus Besar Bahasa Indonesia Serta Implikasinya Pada Teks Puisi Di SMP Negeri 4 Medan - Hutagalung, Santa Hoky; Panggabean, Sarma; Wulan, Eka Putri Saptari (Jurnal Kajian Ilmu Pendidikan (JKIP), 2024)
Meaning is what describes part of culture or the reality of the universe, and in a set of lexical elements, namely the actual meaning or meaning in the dictionary. The field of meaning of hand and foot activities in the KBBI needs to be researched because every day the activities carried out by humans are always related to the hands and feet. All these activities have different lexemes. This research aims to describe the components of the field of lexical meaning of hand and foot activities in the Big Indonesian Dictionary, and to find out the lexemes that describe hand and foot activities and their implications for poetry texts in State Middle Schools. 4 Terrain. The approach used in this research is qualitative using reading and note-taking methods, as well as several advanced techniques that suit field needs. The results obtained from this research are 20 meaning subfields (72 lexemes) of hand activities, 11 lexemes of foot activities contained in the Big Indonesian Dictionary (KBBI), and their implications for poetry texts at SMP 4 Medan.